The use of systems thinking to deal with managing change in the context of the new South Africa - Weston, Ian James; Weston, Ian James (Department of Mechanical Engineering, 2017)
The case study afforded an opportunity to demonstrate how divergent opinions of various stakeholders could be harnessed and synthesised to provide input to resolve perceived problematical situations. In the case study of the hard systems method, ISM, divergence of the stakeholder views was through the process intended to achieve convergence (consensus) in order to solve the problem situation. In the case of the soft systems method, SSM, divergence of views were synthesised to produce an all embracing solution Of the perceived situation. No attempt is made to produce consensus. Systems thinking, therefore, is able to deal with issues that have given known-to-be desirable ends (hard systems) and where known-to-be desirable ends (soft systems) cannot be taken as given. This research has attempted to address the issue of managing the complexity of development in the context of the recently democratised South Africa. It has basically suggested that, as a point of departure, developmental issues should be approached holistically and systematically. It is important to select an appropriate methodology in seeking to solve the problem of managing change. The quality of the outcome of the two case studies reviewed has been affected by the quality of the inputs, particularly with respect to availability of time, availability of stakeholder inputs and the status of the research (that is, as an academic exercise).